Analisis Rantai Nilai Agribisnis Cabai Merah Besar (Studi Kasus di Desa Sindulang, Kecamatan Cimanggung, Kabupaten Sumedang, Provinsi Jawa Barat) - Kuswatim, Salsabila Hanifa; Renaldi, Eddy (Universitas Galuh, 2024)
Capsicum annum are a horticultural commodity that has commercial value. In distributing Capsicum annum, several actors are needed to form a chain. In this chain there are activities that create added value from farmers' production, thus making the price of Capsicum annum different for each actor. This research was conducted with the aim of knowing the agribusiness value chain for Capsicum annum commodities. The location used as the research site is Sindulang Village, Cimanggung District, Sumedang Regency, West Java Province. This research uses a qualitative approach. Informants are selected randomly purposive with technique snowball sampling. The research results will be analyzed using cost of production analysis and the Hayami method. There are 2 business models in Sindulang Village with different value chains, namely the independent farmer business model and cooperative partner farmers. The Cost of Production (HPP) of the independent farmer business model is smaller compared to the HPP of company partner farmers. Independent farmers have a HPP of IDR 10,567/kg, while the HPP obtained from the cooperative partner farmer business model is IDR 15,308/kg. The marketing institution that has the highest added value is the small collecting trader with a value of IDR 4,323, where other marketing institutions such as large collecting traders and cooperatives get a value of IDR 1,721 and IDR 1,440. Based on analysis farmer’s Share, It is known that the most efficient marketing channels in Sindulang Village occur in marketing channels 2 and 3, namely independent farmers who sell Capsicum annum to collectors and farmers who sell Capsicum annum to cooperatives with a percentage of 45%. Meanwhile, farmers who sell to small traders only earn farmer’s share by 35%.